Solar radiation modelling and measurement techniques in Lafia Zone, Nasarawa state, Nigeria - Mamman, Andah (Tanjong Malim, 2020)
Solar radiation modelling and measurement techniques in Lafia Zone, Nasarawa state, Nigeria by Mamman, Andah